Crack growth analysis of carbon nanotube reinforced polymer nanocomposite using extended finite element method. (March 2019) - Negi, Alok; Bhardwaj, Gagandeep; Saini, JS; Grover, Neeraj
In this work, the crack growth analysis of carbon nanotube reinforced polymer nanocomposite has been performed using extended finite element method. The equivalent properties such as elastic modulus, Poisson's ratio, fracture energy, and fracture toughness of the polymer nanocomposites have been evaluated by varying the percentage of carbon nanotube in terms of weight (both single-walled carbon nanotube and multi-walled carbon nanotube) in the polymer matrix. The elastic modulus of the polymer nanocomposite has been evaluated using modified Halpin–Tsai equation. The fracture energy of the polymer nanocomposite has been computed considering carbon nanotube pull-out and carbon nanotube debonding as the main toughening criterion. In the extended finite element method, the crack faces are modeled by discontinuous Heaviside jump functions, whereas the singularity in the stress field at the crack tip is modeled by crack tip enrichment functions. The value of stress intensity factor is evaluated using the domain form of interaction integral. The level set method has been used to track the crack growth. The numerical examples with an edge and a center crack in the polymer nanocomposite are analyzed and the influence of various parameters such as percentage of carbon nanotube and the aspect ratio on stress intensity factor are observed.